Peking University's Personnel Reforms - Yang, Rui (International Higher Education, 2010)
In 2004, Peking University planned a radical overhaul of its faculty appointment and promotion policies. The reform program went far beyond the sphere of personnel itself and received a strong response not only on campus but throughout the country. The developments have vividly portrayed the difficulties and obstacles in China's new policies for universities in a context of globalization and helped to identify further directions and dynamics.